Operator 4.0 and Cognitive Ergonomics - Fallaha, Mohamad (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
With the dawn of industry 4.0, a paradigm shift must occur where the traditional work environment and manufacturing proclivities must transform into a dynamic cyber-physical systems where humans and machines work together for increased productivity and flexibility. This novel and unique work relationship will require unconventional interactions between operators and machines, which will inevitably necessitate an upgrade from the traditional operator to Operator 4.0 or Smart Operator. Engineers and operators must ameliorate their cognitive skills to adapt to Industry 4.0 working environment. Also, smart operators will be required to obtain certain cognitive skills pertaining to wearable technology, sensors or virtual reality equipment as this equipment enhances cognitive capabilities of the Operator 4.0. This research thesis bestows an analysis of Industry 4.0. And provide an evaluation of the topical state of cognitive ergonomics of Smart Operator or Operator 4.0. Considering the importance of VR applications in manufacturing, this research aims to find the cognitive skills required for Operator 4.0 in future factories. The methodology used in this research is based on a factory simulation in Virtual Reality environment. The simulation is similar to Industry 4.0 factories. Participants’ feedback and responses to the given task will help further emphasize how useful can VR in manufacturing be of a help to train future workers. Also, it can assist future designers to avoid any Graphical User Interface (GUI) issues (such as defaults in the 3D simulation as well as the controller software that is used to control the machines) and to improve the quality of such application for a better and more convenient experience. Keywords: Industry 4.0, Operator 4.0, Cognitive Ergonomics, Virtual Reality, Augmented Operator, Cyber-Physical Systems (CPS), Internet of Things (IoT), Big Data, Artificial Intelligence (AI), Smart Factory

ÖZ: Industry 4.0 (I 4.0) doğuşu ile geleneksel iş çevresi ve üretim eğiliminin bir paradigma kayması ile dinamik, siber-fiziksel sistemlere yönelmesini gerekmektedir. Bu sayede insanlar ve makineler üretim ve esnekliğin artması için birlikte çalışmaktadır. Bu yeni ve benzersiz iş ilişkisi, uygulayıcıların ve makinelerin geleneksel olmayan etkileşimine ihtiyaç duyacaktır. Bu nedenle geleneksel uygulayıcıdan Operator 4.0'a veya Smart Operator 'e yükseliş kaçınılmaz bir ihtiyaçtır. Mühendisler ve uygulayıcılar Industry 4.0'ın iş ortamına ayak uydurmak için bilişsel becerilerini geliştirmelidirler. Ayrıca, Smart Operator'lerin giyilebilen teknoloji, sensörler veya sanal gerçeklik ile ilgili belirli bilişsel becerilere sahip olmaları gerekmektedir. Çünkü bu donanımlar Operator 4.0'ın bilişsel işlem kabiliyetini artırmaktadır. Bu araştırma makalesi, Industry 4.0 analizini ve Smart Operator veya Operator 4.0'ın bilişsel ergonomisinin güncel durum değerlendirmesini sunmaktadır. Sanal gerçeklik uygulamalarının üretimdeki önemi düşünüldüğünde bu araştırma gelecekteki fabrikalarda Operator 4.0’ün ihtiyacı olan bilişsel becerileri tespit etmeyi amaçlamaktadır. Bu araştırmada yöntem olarak Sanal Gerçeklik (VR) ortamında bir fabrika simulasyonu kullanılmıştır. Simulasyon, Industry 4.0 fabrikalarına benzerlik göstermektedir. Katılımcıların verilen göreve geri bildirimleri ve cevapları gelecekteki işçileri eğitmede VR’ın ne kadar kullanışlı olduğunu vurgulamaya yardımcı olacaktır. Buna ek olarak, gelecekteki tasarımcılara Grafiksel Kullanıcı Arayüzü (GUI) sorunlarından (örneğin 3D simulasyon hataları ve de makineleri kontrol etmede kullanılan yazılımdaki hatalar) kaçınmada ve daha iyi ve elverişli bir deneyim için böyle bir uygulamanın kalitesini artırmaya yardımcı olabilecektir. Anahtar Kelimeler: Industry 4.0, Operator 4.0, Kognitif Ergonomi, Sanal Gerçeklik, Geliştirilmiş Operatör, Siber-Fiziksel Sistemler (CPS), Internet of Things (IoT), Big Data, Yapay Zeka (AI), Akıllı Fabrika
Master of Science in Industrial Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Industrial Engineering, 2019. Co-Supervisor: Assoc. Prof. Dr. Qasim Zeeshan, Supervisor: Assoc. Prof. Dr. Orhan Korhan.
Keywords: Industrial Engineering; Human engineering--Work environment--Industrial safety; Work--Ergonomics; Industry 4.0; Operator 4.0; Cognitive Ergonomics; Virtual Reality; Augmented Operator; Cyber-Physical Systems (CPS); Internet of Things (IoT); Big Data; Artificial Intelligence (AI); Smart Factory